Clinical and laboratory characteristics of HIV infection as a mono- infection and against the background of intestinal leukemia - Ergasheva Munisa Yakubovna; Achilova Matlyuba Mirkhamzaevna; Vahobova Nilufar Shaxobidinovna (Genius Journals, 2022)
An invasive disease caused by Giardia. In humans, Giardia is caused by Lamblia intestinalis. There are motile (vegetative) and non-motile (cyst) forms of Giardia. The source of the disease is a person infected with giardia. Giardia enters the gastrointestinal tract of a healthy person, multiplies in the small intestine and damages its mucous membrane. They pass from the small intestine to the large intestine (this place is unfavorable for them), lose their movement and turn into cysts. They come out with feces. Giardia cysts are well preserved in the external environment. The disease is transmitted by eating food (especially fruits and vegetables) contaminated with giardia and drinking water, as well as through dirty hands and household items. Cysts are found in faeces in 5- 12% of cases among adults in different geographical regions. Giardia mostly occurs in children. Clinical signs vary depending on the organ affected. More intestinal and bile ducts are affected. Sometimes the symptoms of the disease are not visible, enteritis, cholecystitis, etc. can also go together. During the examination, cysts of giardia can be found in feces, and its vegetative forms can be found in grass (bile). Strict adherence to personal hygiene rules is required to prevent giardia. Treatment: depending on the course of the disease, trichopol, furazolidone, aminaquinol and others are prescribed. In Uzbekistan, various aspects of Giardia were thoroughly studied by Professor N. A. Dehkankhojayeva
Keywords: Giardiasis; Parasitology; Pediatrics; Infection